THREE-LAYER REINFORCED CONCRETE WALL PANELS FROM LIGHT AND HEAVY CONCRETE FORCIVIL BUILDINGS (World Bulletin of Management and Law, 2022)
Assembling buildings is the next step in the transition from elements to construction. In such buildings, external and internal walls, partitions and roofs, curtain walls, stair marches and platforms are produced from large panels. But such large panel constructions are not without some drawbacks. One of the biggest disadvantages of such constructions is high production efficiency. In today's environment of energy resource problems, such shortcomings are again visible. But such constructions cannot be completely abandoned. The reason is that when building buildings from such large wall-panel constructions, the number of assembly operations is drastically reduced, and construction periods are significantly reduced. Therefore, it is necessary to reduce the heat transfer coefficient of such structures either during the production process or during the renovation process. This article presents developments on improving the energy efficiency of buildings. The energy efficiency of some structures was also analyzed
Keywords: Large wall panels; Energy efficient constructions; heat transfer coefficient